Automated Purification and Quantification of Oligonucleotides. (October 1999) - Ivanetich, K.M.; Reid, R.C.; Ellison, R.; Perry, K.; Taylor, R.; Reschenberg, M.; Mainieri, A.; Zhu, D.; Argo, J.; Cass, D.; Strickland, C.
We have developed automated methods for the trityl-on purification and quantification of synthetic oligonucleotides. Oligonucleotide purification is by solid-phase extraction cartridges using Amberchrom ® CG-50 resin on an XYZ-axis robotic system. Quantification is by OD260nm using an online UV-visible spectrophotometer with sipper. The purification of 20 oligonucleotides requires 5 min of user set-up time, plus 20 min per sample of robot time. For a 15–25-mer at the 40 nmol scale of synthesis, the method gives a yield of 2.8 ODs from a load of 10.1 OD, i.e., a 28% average yield. Oligonucleotides purified by this method have proven to be successful for primers for automated DNA sequencing.